Phase Composition of Electrodeposited Fe—Zn Alloys - Kolesnyk, Ie.V. (Металлофизика и новейшие технологии, 2015)
Presence of α-phase, Fe₇₅Zn₂₅, Fe₃Zn₁₀ and η-phase in electrodeposited Fe—Zn alloys is determined by the method of X-ray diffractometry. The phase proportion varies with the increase of zinc concentration in the sulphate electrolyte. Discovered formation of Fe₇₅Zn₂₅ phase during co-deposition of iron and zinc can be the cause of creation of previously revealed irregular surface relief with anomalously high roughness. Revision of Fe₇₅Zn₂₅ phase atomic composition is accomplished by the numerical method based on precise value of the crystal-lattice spacing and taking into account elastic strain caused by zinc atoms, which are dissolved in the α-Fe crystal lattice. Методою рентґенівської дифрактометрії визначено наявність в електроосаджених стопах Fe—Zn α-фази, Fe₇₅Zn₂₅, Fe₃Zn₁₀ та α-фази. Співвідношення фаз змінюється з ростом концентрації цинку в сульфатному електроліті. Виявлене вперше формування фази Fe₇₅Zn₂₅ при сумісному електроосадженні заліза та цинку може бути причиною утворення виявленого раніше нереґулярного рельєфу поверхні з аномально високою шерсткістю. Уточнення складу фази Fe₇₅Zn₂₅ здійснено чисельною методою, виходячи з прецизійного значення періоду ґратниці та з урахуванням пружньої деформації, яку зумовлено атомами Цинку, розчиненими в ґратниці α-Fe. Методом рентгеновской дифрактометрии установлено наличие в электроосаждённых сплавах Fe—Zn α-фазы, Fe₇₅Zn₂₅, Fe₃Zn₁₀ и η-фазы. Соотношение фаз изменяется с ростом концентрации цинка в сульфатном электролите. Обнаруженное впервые формирование фазы Fe₇₅Zn₂₅ при совместном электроосаждении железа и цинка может быть причиной образования выявленного ранее нерегулярного рельефа поверхности с аномально высокой шероховатостью. Уточнение состава фазы Fe₇₅Zn₂₅ выполнено численным методом, исходя из прецизионного значения периода решётки и с учётом упругой деформации, которая обусловлена атомами цинка, растворёнными в решётке α-Fe.